Rasionalitas Masyarakat di Ruang Siber - Ruysdi, Shania Sanra; Al Husna, Dzulfikri (Mekomda: Media Komunikasi Dakwah, 2024)
The focus of the study in this paper wants to try to examine the concept of rationality that underlies a person's actions and its relationship with cyberspace as a new habitat, where people interact with each other. By understanding this, it is hoped that it can provide an overview of how cyberspace and all its consequences, as well as how people act in it from the perspective of the concept of rationality. And it is hoped that the findings can be useful to produce suggestions that can support the smooth running of da'wah. The study in this paper uses qualitative methods and literature, namely interpretatively examining texts obtained from document sources. And it can be found that rationality talks about how an action is carried out by a person on the basis of the knowledge he has, which is oriented towards his goals. Meanwhile, cyberspace is a virtual space that can make it easier for humans to interact and communicate even though in real time and space. However, this convenience is also accompanied by risks such as cybercrime or cyberbullying. So ideally, people should have rationality when entering cyberspace. In order to be able to domesticate the information and communication technology that makes them connected to cyberspace, and benefit from it.